Safety profile of Td vaccination in Indonesian pregnant women: a post-marketing surveillance study (Medical Journal of Indonesia, 2019)
BACKGROUND The Indonesian Expanded Program of Immunization has implemented tetanus and diphtheria (Td) vaccination to replace the tetanus toxoid vaccine in pregnant women since the year 2016. Td vaccine is administered to protect against diphtheria and tetanus to the mother and her baby as well. This prospective study was conducted to assess the adverse reactions after Td immunization; besides, a retrospective study was conducted to observe the presence of severe local reaction (Arthus reaction), premature birth, and low birth weight history in the medical records of pregnant women who had received Td immunization in the past year. METHODS A prospective observational study was conducted in 200 pregnant women. Local reactions and systemic events occurring within 28 days after immunization were recorded in the diary card and were confirmed by the health worker in the follow-up visit. A retrospective study was also conducted to evaluate 750 medical records of pregnant women who had received Td immunization. The study was conducted from September 2017 to January 2018. The study has been registered at ClinicalTrials.gov ID: NCT03383653. RESULTS In 185 pregnant women who completed the study, the most common local reaction was pain, occurring in 33.5% of subjects within 24 hours after vaccination. Fever, other systemic reactions, and serious adverse events were not reported during the observation. In the retrospective study, 647 medical records were validated. No Arthus reaction was observed. The prevalence of premature birth was 1.24%, and that of low birth weight was 2.63%, which were below the normal rates. CONCLUSIONS Td vaccination in pregnant women was safe and well-tolerated.